Children's play activities viewed from the geographical location aspect - Gusril; Anton Komaini; Fitrah Arrasyih; Toho Cholik Mutohir; Mohd Salleh Aman; Ahmad Chaeroni; Heru Andika (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The problem of this research is the low level of children's play activity in terms of geographical location. This can be seen from the category of children's play activities in the city of Padang which is in the sufficient category. This is because parents are too overprotective of their children in playing activities. Parents are more likely to have their children help their parents work, study and recite the Koran. The objectives of this research: (1) To reveal children's play activities from the highlands; (2) To reveal the play activities of lowland children; (3) To reveal children's beachside play activities; (4) To reveal the effectiveness of children's play activities in terms of highland, lowland and beachside aspects. This research method uses comparative quantitative research (comparison). The research population was highland elementary school students (Tanah Datar Regency), lowland (Padang City), Padang Experimental State Elementary School students, Kampung Jawa Elementary School students, Pariaman City (coastal plain). Samples were drawn using purposive sampling and a sample of 106 people were obtained from the highlands, lowlands and seaside. The instrument used to measure Gusril's Play Activities contains closed questions on a Likert scale with a validity of 0.69 and a reliability of 0.94 as well as open questions to capture data that has not been captured by a closed questionnaire for children in the highlands (Bukittinggi), lowland (Padang City) and the beach (Kota Pariaman). The data analysis technique for this research uses Descriptive and Inferential Oneway Anova statistics to test the effectiveness of children's play activities. Based on data analysis and discussion, the following research results can be concluded: (1) Highland children's play activities are in the very good category; (2) Lowland children's play activities are in the sufficient category; (3) Beachside children's play activities are in the sufficient category; (4) Highland children's play activities are more effective than lowland and beachside areas. (5) There is no significant difference between lowland and beachside play activities. It is recommended that parents give their children the opportunity to play because playing is a child's human right according to the 2003 Geneva Sports and Health Conference.